Zoom surprising ways to supercharge your career - Roberts, Daniel (Fortune Books, an imprint of Time Home Entertainment Inc., 2013)
Foreword / Marc Andressen -- Introduction / Leigh Gallagher -- 1. Challenge Goliath / Kevin Plank, Katrina Markoff, John Janick -- 2. Get in over your head / Marissa Mayer, Elon Musk, Meredith Whitney -- 3. Start a cult / Tony Hsieh, Larry Page, Sergey Brin, Eric Ryan, Adam Lowry -- 4. Follow your first love / David Chang, Kevin Fiege, Seth Macfarlane -- 5. Find a problem / Jennifer Hyman, Jennifer Fleiss, Perry Chen, Yancey Strickler, Charles Adler, Brian Chesky -- 6. Do one thing well / Jess Lee, Kevin Systrom, Biz Stone, Ev Williams -- 7. Stand by your company / Dolf van den Brink, Rob Goldstein , Aditya Mittal -- 8. Think of others / Scott Harrison, Ben Rattray, Blake Mycoskie -- 9. Bounce back / Hosain Rahman, Boaz Weinstein, Lebron James -- In their own words: tips and advice from zoomers -- Appendix: Where are they now? The 40 under 40 class lists.